Mobility of public schools personnel of Western Mindanao - Allian, Nassal M.
The mobility trend among 5,130 public school teachers varies with respect to sex, age, years of service, family size, ethnicity and educational level. Vertical mobility requires competence and qualifications and candidates for this form of mobility must satisfy personal and professional requirement such as chronological maturity and a high degree of loyalty and commitment to the system. Respondents intend to transfer to other agencies of the government for legitimate reasons, such as more chances for promotion, higher salary, more varied and challenging activities, more opportunities for travel under government expense, optimum workload, more favorable working conditions and less professional requirements.